2019
DOI: 10.3390/f10010043
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Fuel Consumption and CO2 Emissions of Excavator-Based Harvesters with a Machine Control System

Abstract: Compared with purpose-built units, excavator-based harvesters offer many advantages, but they also face one main limitation: a much higher fuel consumption, which also results in higher CO2 emission levels. The fuel efficiency of excavator-based harvesters can be increased by a better interface between the excavator and the harvester head. This study aimed to determine the performance of a new adaptation kit, specifically designed to improve the communication between these two components. The new kit offers re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…As a result, detailed information from the studied CTL harvesting machines is presented in Article I and showed that extreme machine settings had a statistically significant impact on fuel economy. This is generally similar to a recently published study on reduced fuel use of excavator-based machines using a machine control system (Spinelli and Moura 2019). Nevertheless, the results show some indication that the currently used business-as-usual setting may already integrate characteristics of the ECO mode regarding fuel economy in regular operations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As a result, detailed information from the studied CTL harvesting machines is presented in Article I and showed that extreme machine settings had a statistically significant impact on fuel economy. This is generally similar to a recently published study on reduced fuel use of excavator-based machines using a machine control system (Spinelli and Moura 2019). Nevertheless, the results show some indication that the currently used business-as-usual setting may already integrate characteristics of the ECO mode regarding fuel economy in regular operations.…”
Section: Discussionsupporting
confidence: 90%
“…Thereby the parameters most influencing the performance could be identified, and consequently also modified according to operational needs. In addition, other machines could be tested with different machine settings for fuel consumption and energy efficient performance, for example, forwarders in CTL harvesting or excavators, which could also be similar to the excavator-based harvesting system and machine control system presented recently by Spinelli and Moura (2019). Moreover, machine setting tests could also be conducted under other silvicultural prescriptions or stand characteristics.…”
Section: Future Research Notesmentioning
confidence: 99%
“…Ackerman et al 2017, Prinz at al. 2018, Hudiburg et al 2019, Spinelli and de Arruda Moura 2019, Domke et al 2020, such as EPA ( 2016), the factors are almost the same and hence the results and conclusions of the study are comparable to them. In addition, the emission factors are applicable to calculating GHG emissions and energy efficiencies in future emissions investigations.…”
Section: Energy Efficiency Of Wood-harvesting Operationssupporting
confidence: 61%
“…To increase the productivity of the equipment, Spinelli and Moura (2019) tested an adaptation kit, specifically designed to improve communication between the harvester head and the excavator. According to the authors, there was a 6% increase in equipment productivity.…”
Section: Entrance Of New Technologymentioning
confidence: 99%